2023
DOI: 10.1007/s40279-023-01878-1
|View full text |Cite
|
Sign up to set email alerts
|

Data Informing Governing Body Resistance-Training Guidelines Exhibit Sex Bias: An Audit-Based Review

Abstract: The objective of this review was to examine the ratio of female and male participants utilised in data informing consensus statements and position stands in the field of resistance training (RT). In order to achieve this objective, we conducted an ‘audit’ style review. We accessed three databases: SPORTDiscus, MEDLINE and Google Scholar utilising the following search terms: resistance or strength training AND consensus statements or position statements/stands. Eligibility criteria included consensus statements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Among potential benefits, resistance training is an effective intervention for increasing muscle strength (47), power (6), and size (47,48) as well as reducing fat mass (48). However, substantial evidence indicates that women are under-represented in the resistance training literature (17,57,59), resulting in limited resistance training recommendations (59). A previous review analyzing 1,382 articles involving 6,076,580 participants in the Sport and Exercise Medicine area indicated that only 39% were women (17).…”
Section: Introductionmentioning
confidence: 99%
“…Among potential benefits, resistance training is an effective intervention for increasing muscle strength (47), power (6), and size (47,48) as well as reducing fat mass (48). However, substantial evidence indicates that women are under-represented in the resistance training literature (17,57,59), resulting in limited resistance training recommendations (59). A previous review analyzing 1,382 articles involving 6,076,580 participants in the Sport and Exercise Medicine area indicated that only 39% were women (17).…”
Section: Introductionmentioning
confidence: 99%